Iterates of Bernstein Type Operators on a Triangle with All Curved Sides - Teodora Cătinaş (Abstract and Applied Analysis)
We consider some Bernstein-type operators as well as their product and Boolean sum for a function defined on a triangle with all curved sides. Using the weakly Picard operators technique and the contraction principle, we study the convergence of the iterates of these operators.